AKTIVITAS ANTIPIRETIK KONSENTRAT AIR KELAPA (COCOS NUCIFERA L.) MUDA TERHADAP TIKUS WISTAR JANTAN YANG DIINDUKSI DEMAM DENGAN PEPTON - Alfarishi, Femi
Fever is a symptom of a disease characterized by an increase in body temperature above normal, usually above 37.5 o C. Empirically, young coconut water is used to treat fever. However, there is not much report of antipyretic activity of young coconut water scientifically. This study was conducted to determine the antipyretic activity of the concentrate of coconut water. A total of 24 male Wistar rats were divided into six groups: normal, control, paracetamol 50 mg/kg bw, K275 (concentrate of young coconut water 275 mg/kg bw), K550 (concentrate of young coconut water 550 mg/kg bw), and K1100 (concentrate of young coconut water 1100 mg/kg bw). Fever was induced by administering 125 mg/kg bw of peptone subcutaneously. Body temperature was measured before induction with peptone (t0), one hour after induction with peptone (t1), one hour after administration of the test substance (t2), two hours after administration of the test substance (t3), and three hours after administration of the test substance (t4). There were significant differences in paracetamol, K275, K550, and K1100 groups at t2 compared to its temperature at t1, with the average decrease in body temperature of 1.13 o C, 0.43 o C, 0.63 o C, and 0.73 o C, respectively. K1100 group showed antipyretic activity similar to paracetamol group at t2, t3, and t4.